Pemanfaatan Tanaman Toga Sebagai Upaya Peningkatan Kesehatan Masyarakat Desa Kudu Ganting - Aprilya Dwi Nur'aini; Aura Giaska Andiny; Haril Saleleubaja; Muhammad Renggi Saputra; Taupik Hidayat; Rakimahwati (STIKes Ibnu Sina Ajibarang, 2026)
Family Medicinal Plants (TOGA) are one form of natural resource utilization that can be used as an alternative traditional medicine as well as an effort to improve public health. Medicinal plants are widely used by the community because they are easy to obtain, relatively safe, and have lower costs compared to modern medical drugs. This study aims to examine the utilization of TOGA plants as an effort to improve the health of the people of Kudu Ganting Village through a literature study approach. The method used was a literature review by examining various scientific sources such as books, journals, and research reports related to family medicinal plants. The results of the study indicate that plants such as ginger, turmeric, lemongrass, temulawak, and betel leaves provide various health benefits, including improving body immunity, treating digestive disorders, and functioning as natural antiseptics. Therefore, the utilization of TOGA plants can serve as an effort to improve community health while also making productive use of home yard land.